Respuesta :

Answer:

D

Step-by-step explanation:

A)

3(2) + 4(-2) = -2                    2(2)-4(-2) = -8

6 - 8 = -2                              4 + 8 = -8

Correct                                 Incorrect  

B)

3(6) + 4(-5) = -2                    2(6) - 4(-5) = -8  

18 - 20 = -2                            12 + 20 = -8

Correct                                 incorrect

C)

3(4) + 4(4) = -2

12 + 8 = -2

incorrect

D)

3(-2) + 4(1) =-2                        2(-2) - 4(1) = -8

-6 + 4 = -2                                 -4 - 4 = -8

Correct                                      Correct

Best way is process of elimination